Transfemoral Occlusion of Doubly Committed Subarterial Ventricular Septal Defect Using the Amplatzer Duct Occluder-II in Children - Tang, Changqing; Zhou, Kaiyu; Shao, Shuran; Liu, Xiaoliang; Li, Yifei; Hua, Yimin; Wang, Chuan (Frontiers in Cardiovascular Medicine, 2022)
Backgrounds: The traditional treatment of doubly committed subarterial ventricular septal defect (dcVSD) is open-heart surgery. This study aimed to evaluate the feasibility, safety, and outcome of transcatheter closure of small dcVSD using Amplatzer duct occluder-II (ADO-II) in children. Methods: Between January 2016 and April 2021, 24 children (17 male and 7 female patients) with small dcVSD who received transfemoral closure with ADO-II were enrolled retrospectively. All of their available clinical and follow-up data were evaluated. Results: Patients’ median age was 3.2 years (1.6-12.6 years, 4.2 ± 3.1years) and body weight was 13.3 kg (10.0-38.5 kg, 16.5 ± 7.7kg). Left ventricular angiography showed that the median dcVSD size was 2.0 mm (1.5-3.5 mm, 2.1 ± 0.6 mm). The device was successfully implanted in 23 patients (95.8%), and one patient failed to be closed because of the underestimation of defect size due to preoperative aortic valve prolapse, with 16 patients by the antegrade approach and eight patients by retrograde approach. The diameters of the device used were 3/4, 4/4, and 5/4 mm. The median operative time was 40.0 minutes (20.0-75.0 minutes, 41.7 ± 13.7 minutes), and median fluoroscopic time was 5.0 minutes (3.0-25.0 minutes, 6.8 ± 5.0 minutes). With a follow-up duration of 1+ to 45+ months, only 1 patient presented with new-onset mild aortic regurgitation (AR). Conclusions: Transfemoral closure of small dcVSD with ADO-II is technically feasible and safe in selected children. However, development or worsening of AR requires long-term follow-up.